Sport fans the psychology and social impact of fandom - Wann, Daniel L.; James, Jeffrey D. (Jeffrey Dalton) (Routledge/Taylor & Francis Group, 2019)
Sports, and the fans that follow them, are everywhere. Sport Fans: The Psychology and Social Impact of Fandom examines the affective, behavioral, and cognitive reactions of fans to better comprehend how sport impacts individual fans and society as a whole. Using up-to-date research and theory from multiple disciplines including psychology, sociology, marketing, history, and religious studies, this textbook provides a deeper understanding of topics such as: the pervasiveness of sport fandom in society; common demographic and personality characteristics of fans; how fandom can provide a sense of belonging, o uniqueness, and of meaning in life; the process of becoming a sport fan; sport fan consumption; and the future of sport and the fan experience. The text also provides a detailed investigation of the darker side of sport fandom, including fan aggression, as well as a critical look at the positive value of fandom for individuals and society. Sports Fans expertly combines a rigorous level of empirical research and theory in an engaging, accessible format, making this text the essential resource of sport fan behavior